(untitled) (Journal of Guidance and Counselling Studies, 2016)
This paper investigated approaches to resolving clients’ problems in counselling, in a multi-ethnic society as perceived by guidance counselors in Anambra State, Nigeria. The study is a descriptive survey guided by two research questions. The population of the study includes all the 145 Guidance Counsellors in public secondary schools in Anambra State. The whole 145 counsellors equally formed the sample of the study. Questionnaires; “Counsellors’ Perception of Problems of Counselling in a Multi-Ethnic Society’’ (CPPCMESQ) and “Counsellors’ Perception of Approaches to counselling in a Multi-ethnic society” (CPACMESQ) were used to collect data from the respondents using direct delivery approach. Then, the data were collated, scored and analysed using mean and percentage. Findings from the study revealed among others that a higher percentage of the counsellors chose Eclectic, behaviour modification, and integrative approaches to counselling as the suited approaches to counselling in a multi-ethnic society Nigeria. Findings further revealed that problems of counselling in a multi-ethnic society includes; language barrier, tribalism, religion, high level of illiteracy, ethnic prejudice, application of appropriate theory, beliefs, practices and values of the clients, and not recognizing that ethnicity and culture are significant parameters for understanding psychological processes are problems to counselling. Based on the findings, the implication of the study was formed and recommendations made.